2018
DOI: 10.1007/s41315-017-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid FES–robotic gait rehabilitation technologies: a review on mechanical design, actuation, and control strategies

Abstract: Gait disorders in neurologically disabled people can be treated by various techniques available today which include passive orthoses, functional electrical stimulation (FES) and robot assisted gait training devices (RAGT). However, each system has its own drawback. For example, gait rehabilitation with orthosis is physically taxing for the patient with no significant functional improvement. FES uses muscle powers as physiological actuators to promote balance and improve gait but leads to fatigue, along with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 82 publications
0
28
0
Order By: Relevance
“…Wearable robots like exoskeletons are coupled to the user, and the robot moves with the wearer cooperatively (Awad et al, 2017 ; Anaya et al, 2018 ; Bai et al, 2018 ; Fani et al, 2018 ). In this case, the design should be able to follow the human movements minimizing resistive forces felt by the human, i.e., the design should be mechanically transparent.…”
Section: Mechanical Transparencymentioning
confidence: 99%
“…Wearable robots like exoskeletons are coupled to the user, and the robot moves with the wearer cooperatively (Awad et al, 2017 ; Anaya et al, 2018 ; Bai et al, 2018 ; Fani et al, 2018 ). In this case, the design should be able to follow the human movements minimizing resistive forces felt by the human, i.e., the design should be mechanically transparent.…”
Section: Mechanical Transparencymentioning
confidence: 99%
“…Depending primarily on FES alone for gait can be metabolically taxing, is prone to rapid fatigue, and may lack limb control and stability. For these reasons effort has gone into combining FES with orthotic devices, generally called hybrid FES systems, which can provide several advantages relative to using FES alone (Andrews et al, 1988 ; Isakov et al, 1992 ; Goldfarb et al, 2003 ; Bulea et al, 2013 ; del-Ama et al, 2014 ; Chang et al, 2017 ; Anaya et al, 2018 ), and one prior study investigated a hybrid FES system that couples FES with a robotic exoskeleton (Ha et al, 2016 ). That study specifically coupled a lower limb exoskeleton with FES of the quadriceps and hamstrings muscle groups of each leg, and demonstrated reduced exoskeleton motor torque and power when used in a hybrid FES manner.…”
Section: Introductionmentioning
confidence: 99%
“…In this first approach, we take the weighting factors to be the same for both actuators (δ = 0.5). The weighting factors can be associated with the level of assistance in a hybrid orthosis (Anaya et al, 2018). The parameter δ basically represents some priority given to the use of either the FES actuation or the motor actuators.…”
Section: Methodsmentioning
confidence: 99%
“…Using hybrid orthosis to stimulate the lower extremity muscles has proven to evoke muscle hypertrophy, increase strength, improve cardiopulmonary fitness, and reduce fatigue during gait, even in subjects with severe spasticity (Nightingale et al, 2007; Qiu and Taylor, 2016; Deley et al, 2017; Ekelem and Goldfarb, 2018; Lambach et al, 2018). Complete recent reviews of hybrid exoskeletons can be found in Stewart et al (2017) for the upper limbs, and Anaya et al (2018) for the lower limbs.…”
Section: Introductionmentioning
confidence: 99%